2018
DOI: 10.3389/fcimb.2018.00197
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptional Profiling of Immune-Related Genes in Leishmania infantum-Infected Mice: Identification of Potential Biomarkers of Infection and Progression of Disease

Abstract: Leishmania spp. is a protozoan parasite that affects millions of people around the world. At present, there is no effective vaccine to prevent leishmaniases in humans. A major limitation in vaccine development is the lack of precise understanding of the particular immunological mechanisms that allow parasite survival in the host. The parasite-host cell interaction induces dramatic changes in transcriptome patterns in both organisms, therefore, a detailed analysis of gene expression in infected tissues will con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
25
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(27 citation statements)
references
References 92 publications
(138 reference statements)
1
25
0
Order By: Relevance
“…Of the 112 genes studied, 22 showed differential expression in infected vs. uninfected mice. Il12rb2, Il23r, and Ptgs2 were exclusively expressed only in infected mice but not in the control group, suggesting that the immune molecules may vary drastically under the condition when initial priming is done (uninfected) compared to when subsequent infection occurs [190]. Thus, an aim in vaccination is to induce the balanced expression of co-stimulatory and co-inhibitory molecules such that appropriate Th cell priming occurs.…”
Section: Resultsmentioning
confidence: 99%
“…Of the 112 genes studied, 22 showed differential expression in infected vs. uninfected mice. Il12rb2, Il23r, and Ptgs2 were exclusively expressed only in infected mice but not in the control group, suggesting that the immune molecules may vary drastically under the condition when initial priming is done (uninfected) compared to when subsequent infection occurs [190]. Thus, an aim in vaccination is to induce the balanced expression of co-stimulatory and co-inhibitory molecules such that appropriate Th cell priming occurs.…”
Section: Resultsmentioning
confidence: 99%
“…This controversy may be explained by the fact that different patterns of gene expression are found in macrophages at different time points ( 130 ). A recent study demonstrated that the early response against L. donovani infection was distinguished by the increase in of Th1 markers and M1-macrophage activation molecules (IFN-γ, Stat1, Cxcl9, Cxcl10, Ccr5, Cxcr3, Xcl1, and Ccl3).…”
Section: M1 and M2 Macrophages In Leishmania Infecmentioning
confidence: 99%
“…However, this activation was not protective because the parasitic burden increased over time. There was no marked overlap of macrophage phenotypes at intermediate times of infection, and the overexpression of these Th1/M1 markers was restored later in the chronic phase without parasitic burden control ( 130 ).…”
Section: M1 and M2 Macrophages In Leishmania Infecmentioning
confidence: 99%
“…Statistically significant differences are indicated (*p < 0.05; **p < 0.01, ***p < 0.001). Global analysis of transcriptome generated under different experimental conditions, has grown increasingly relevant in order to clarify key questions of intricate models like infection of target organs in leishmaniasis (11,13). With the aim of deciphering the most relevant aspects of the response against leishmaniasis developed in liver during the initial phases of infection with L. infantum, a massive real-time quantitative PCR analysis (more than 32000 qPCR reactions) was performed in BALB/c mice.…”
Section: Leishmania Infantum Infection Is Established In Liver 24 H Pmentioning
confidence: 99%
“…Many studies have focused on the analysis of immunological response in the spleen in Leishmania-infected mice, (11)(12)(13), where many mediators play a role in M1/Th1 and M2/Th2 responses, but also markers of T reg response, Th17, and Tfh cells are involved (14). However, understanding the development of immunity in the liver, where infection develops shortly after inoculation, could lead to potential strategies to improve the elimination of the parasite in the spleen (15).…”
Section: Introductionmentioning
confidence: 99%